A combination of three plasma bile acids as a putative biomarker for schizophrenia. Issue 1 (23rd February 2021) - Tao, Yanlin; Zheng, Fang; Cui, Donghong; Huang, Fei; Wu, Xiaojun
Abstract: The aim of the present study is to determine whether plasma bile acids (BAs) could be used as an auxiliary diagnostic biomarker to distinguish patients with schizophrenia from healthy controls. Seventeen different BAs were quantitatively measured in plasma of 12 healthy participants and 12 patients with schizophrenia. Then, the data were subjected to correlation and linear discriminant analysis (LDA). The concentrations of cholic acid (CA), taurochenodeoxycholic acid (TCDCA) and taurodeoxycholic acid (TDCA) were significantly decreased in plasma of the schizophrenia patients. Correlation analysis showed the concentrations of CA, TCDCA and TDCA were negatively correlated with schizophrenia. In addition, LDA demonstrated that combination of CA, TCDCA and TDCA with a classification formula could predict correctly classified cases and the accuracy of prediction was up to 95.83%. Combination of the three BAs may be useful to diagnose schizophrenia in plasma samples.